Dynamics of China's relations with Vietnam - Zivot, Samuel; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
This thesis attempts to evaluate the international relations dynamic that exists between Vietnam and China in order to establish whether future conflict between those countries should be expected. In order to provide a basis from which that outcome can be established this thesis will evaluate the case, including both the historical relations between the two countries and their contemporary activities, utilizing two different international relations theories; Neorealism, as described by Kenneth Waltz in his book Theory of International Politics, and Asymmetry Theory, as described by Brantly Womack in his book China and Vietnam: The Politics of Asymmetry. Consequently, a secondary goal of this thesis is the evaluation of those two theories in the context of their application as predictive theories of international relations as a byproduct of their utility in application to this case.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses